2021
DOI: 10.1038/s41598-021-82869-y
|View full text |Cite
|
Sign up to set email alerts
|

Automatic ganglion cell detection for improving the efficiency and accuracy of hirschprung disease diagnosis

Abstract: Histopathologic diagnosis of Hirschsprung's disease (HSCR) is time consuming and requires expertise. The use of artificial intelligence (AI) in digital pathology is actively researched and may improve the diagnosis of HSCR. The purpose of this research was to develop an algorithm capable of identifying ganglion cells in digital pathology slides and implement it as an assisting tool for the pathologist in the diagnosis of HSCR. Ninety five digital pathology slides were used for the construction and training of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
0
17
0
2
Order By: Relevance
“…So, new studies have emerged aiming to simplify HD diagnosis, revisiting the use of H&E staining in rectal mucosa and submucosa fragments. 16 , 17 , 18 , 19 The detection of ganglion cells in the submucosal plexuses by utilizing H&E staining, as simple as the method might be, still creates a lot of controversies. Several authors cite the difficulty in identifying these cells, since they are diffusely distributed throughout the intestinal submucosa.…”
Section: Introductionmentioning
confidence: 86%
“…So, new studies have emerged aiming to simplify HD diagnosis, revisiting the use of H&E staining in rectal mucosa and submucosa fragments. 16 , 17 , 18 , 19 The detection of ganglion cells in the submucosal plexuses by utilizing H&E staining, as simple as the method might be, still creates a lot of controversies. Several authors cite the difficulty in identifying these cells, since they are diffusely distributed throughout the intestinal submucosa.…”
Section: Introductionmentioning
confidence: 86%
“…Hirschsprung's disease (HSCR) is the most common congenital alimentary tract developmental malformation in children with an incidence ranging between ~ 1/2000 and ~ 1/5000 live births [1,2]. The pathological characteristic of HSCR is completely lack of ganglion cells in submucosal and myenteric plexuses in colon [3], owing to the consequence of the premature arrest of the migration of ectodermal vagal neural crest cells to form the enteric nervous system (ENS) before 12th week of gestation [4,5]. This de ciency leads to peristaltic dysfunction and persistent tetanic contraction within the lesioned colon, nally causing intestinal obstruction [6].…”
Section: Introductionmentioning
confidence: 99%
“…Porém, novos trabalhos têm surgido com o objetivo de simplificar o diagnóstico revisitando o uso da coloração HE nestes fragmentos de mucosa e submucosa retal 8,35,48,50,60 .…”
Section: Discussionunclassified
“…In a recent study, we demonstrated that the analysis of 60 sections per fragment of rectal mucosa and submucosa stained by HE may ensure a 90% diagnostic accuracy. In this study, in 54% of the cases, neurons were found in the final sections (50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). This encouraged us to study their distribution in the rectal submucosa, as a means to simplify the diagnosis.…”
mentioning
confidence: 85%
See 1 more Smart Citation